Rural Reforms, Agricultural Productivity, and the Biological Standard of Living in South Korea, 1941-1974 - Robert Rudolf (Georg-August-Universität Göttingen, Courant Research Centre - Poverty, Equity and Growth (CRC-PEG), 2012)
This paper analyzes effects of the Republic of Korea's two major rural reforms in 1950 and 1962/63 on agricultural productivity and individual well-being. The 1950 Land Reform resulted in a large-scale redistribution of land while 'green revolution'-type reforms in 1962/63 pushed forward the application of modern agricultural technologies and improved rural infrastructure. This study's findings indicate that both reforms had significant positive impacts on agricultural productivity. Using the link between final height outcomes and early childhood nutrition further allows an assessment of the effects of the interventions on the biological standard of living using adult height outcomes. Korean mean adult height grew by a remarkable 8.1 to 12 cm for women and 7 to 9.6 cm for men born between 1920 and 1987. Two thirds of this growth took place after the 1950 reform, and about 40 to 50 percent after the 1962/63 reforms. Structural break analyses of height trends reveal significant upward shifts in trend around the years of the reforms. While Korea can be considered a case of successful land reform, the years between the two major reforms can be considered Korea's lost decade.
Keywords: Q15; N35; O13; 330; Land Reform; Rural Technological Reforms; Agricultural Productivity; Biological Standard of Living; Equity-Efficiency